2013
DOI: 10.1186/1476-511x-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 fatty acids increase the chemo-sensitivity of B-CLL-derived cell lines EHEB and MEC-2 and of B-PLL-derived cell line JVM-2 to anti-cancer drugs doxorubicin, vincristine and fludarabine

Abstract: BackgroundB-Cell chronic lymphocytic leukemia (CLL) is the most common form of leukemia in the United States. Clinical treatment of CLL is often limited due to drug resistance and severe therapy-induced toxicities. We hypothesized that the omega 3 (n-3) fatty acids, eicosapentaenoic acid (EPA) and/or docosahexaenoic acid (DHA), would increase the sensitivity of malignant B-lymphocytes to anti-cancer drugs doxorubicin, vincristine and/or fludarabine in vitro and that increased sensitivity is achieved by alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Fish oil containing 367 mg of EPA and 243 mg of DHA for 9 weeks was sufficient to alter the fatty acid composition of plasma lipid constituents, leading to an approximately two‐fold increment in the proportion of EPA and a 1.8‐fold increase for DHA. The same finding has been reported in previous studies .…”
Section: Discussionsupporting
confidence: 93%
“…Fish oil containing 367 mg of EPA and 243 mg of DHA for 9 weeks was sufficient to alter the fatty acid composition of plasma lipid constituents, leading to an approximately two‐fold increment in the proportion of EPA and a 1.8‐fold increase for DHA. The same finding has been reported in previous studies .…”
Section: Discussionsupporting
confidence: 93%
“…Only three studies were found reporting that DHA treatment affects transition through the S phase of the cell cycle. In the hepatocarcinoma cell line MHCC97L, 50 μM DHA was found to disrupt and prolong S phase transition [ 22 ]. In this experiment, cells were BrdU-labelled and DNA synthesis time, based on the relative movement of cells through the cell cycle, was measured.…”
Section: Effect Of Docosahexaenoic Acid On Cell Cycle Progressionmentioning
confidence: 99%
“…The time to progress through S phase increased from 18 to 21 h after DHA treatment. In particular, the proportion of Jurkat leukemia cells in the S phase of the cell cycle (measured at 0 and 24 h) increased from 30% to 68% with 30 μM DHA treatment while G1 decreased (62% to 43%) [ 22 ]. Control cells had a larger proportion of cells moving to G2 than the DHA treatment (11% vs. 2%), suggesting that cells were continuing to move through the cell cycle compared to the DHA cells that were accumulating in S phase [ 20 ].…”
Section: Effect Of Docosahexaenoic Acid On Cell Cycle Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, three conjugates have entered clinical trials and hold a great potential to be applied in clinicals in the future, including docosahexaenoic acid (DHA)‐paclitaxel (PTX), elaidic acid‐cytarabine, and elaidic acid‐gemcitabine . The rational design of UFAs‐based conjugates can be attributed to the following aspects: (i) to enhance the stability of anticancer drugs, the conjugation of anticancer drugs with UFAs can protect the fragile groups of the parent drug from being metabolized in vivo; (ii) to improve lipophilicity of drugs, hydrophilic drugs cannot easily pass through the bilayer membrane via passive diffusion, resulting in poor bioavailability in target sites; (iii) to achieve natural targeting effects to tumors, several studies have suggested an increased fatty acid uptake in tumors as nutrient sources; (iv) to enhance the chemotherapeutic response of anticancer drugs, some UFAs could significantly sensitize anticancer drugs‐induced apoptosis of human tumor cells; and (v) to minimize side effects of anticancer drugs at high doses, low cytotoxicity and sustained release of the parent drugs make UFAs‐based anticancer conjugates reduced side effects. Therefore, developing advanced UFAs‐based DDS holds great potential for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%